Angiotensin receptor blocker reduces proteinuria independently of blood pressure in children already treated with Angiotensin-converting enzyme inhibitors - Seeman, Tomás; Pohl, Michael; Misselwitz, Joachim; John, Ulrike (Kidney & blood pressure research, 2009)
BACKGROUND/AIMS: Dual blockade of the renin-angiotensin system with angiotensin-converting enzyme inhibitors (ACEI) and angiotensin receptor blockers (ARB) has higher antiproteinuric effects than single blockade in adults. In children, little is known on dual blockade of the renin-angiotensin system. The study investigates whether adding an ARB to proteinuric children already on ACEI reduces proteinuria. METHODS: A total of 10 children (median age 13.3 years) with chronic kidney disease and persistent proteinuria despite maximal dose of ACEI were included. Losartan was given at an initial dose 0.8 mg/kg/day. Proteinuria, blood pressure (BP) and renal function (glomerular filtration rate) were measured. RESULTS: Mean proteinuria decreased from 484 +/- 290 mg/mmol creatinine to 223 +/- 197 after 1-3 months of losartan treatment and remained stable at 234 +/- 153, 224 +/- 177 and 195 +/- 133 after 3-6, 6-12 months and at the last follow-up check (median 1.9 years, p < 0.05 for all visits vs. before treatment). The median percentage decrease in proteinuria was 66, 56, 44 and 66% during the study periods. No significant change in BP, glomerular filtration rate or serum potassium was observed. One child complained of rash, which led to discontinuation of losartan. CONCLUSION: Adding an ARB to current ACEI treatment can further reduce proteinuria in children with chronic kidney disease without affecting BP.
Keywords: Potassium; Male; Child, Preschool; draslík; Kidney Failure, Chronic; Glomerular Filtration Rate; losartan; Adolescent; chronické selhání ledvin; blokátory receptorů AT1 pro angiotensin II; kombinovaná farmakoterapie; Child; inhibitory ACE; dítě; Creatinine; mužské pohlaví; krevní obraz; Drug Therapy, Combination; Angiotensin-Converting Enzyme Inhibitors; mladiství; Kidney Function Tests; předškolní dítě; Blood Cell Count; proteinurie; lidé; krevní tlak; ženské pohlaví; Humans; Blood Pressure; kreatinin; vyšetření funkce ledvin; Angiotensin II Type 1 Receptor Blockers; Proteinuria; hodnoty glomerulární filtrace; Female; Losartan